Baicalein targets CD36 to prevent foam cell formation by suppressing the excessive uptake of oxLDL and accelerating ABCA1-mediated cholesterol efflux in oxLDL-induced THP-1 macrophages. (October 2022) - Li, Jingda; Xiong, Tao; Wang, Tianqi; Wang, Meng; Wang, Chao; Yang, Fuyuan; Wang, Xudong; Tan, Zhijian; Sun, Wenlong
Graphical abstract: Highlights: Baicalein can prevent oxLDL-induced foam cell formation in THP-1 macrophages. Baicalein inhibits oxLDL uptake by preventing the binding of CD36 to oxLDL. The binding of baicalein to CD36 triggers the Src-JNK-ABCA1 signalling pathway. Baicalein enhances cholesterol efflux to avoid cholesterol accumulation. Abstract: Oxidized low-density lipoprotein (oxLDL)-induced macrophage foam cell formation plays an important role in atherosclerosis progression. Baicalein is a constituent of Scutellaria baicalensis. Herein, we investigated the effect of baicalein on macrophage foam cell formation and the underlying mechanism. The THP-1 macrophage foam cell was established by oxLDL stimulation and the effects of baicalein on cholesterol uptake and efflux were analysed by molecular docking, ELISA, immunofluorescence, western blot, the inhibitor and siRNA experiment. The results showed that baicalein suppressed oxLDL-induced cholesterol accumulation. Mechanistically, baicalein reduced oxLDL uptake through competitive inhibiting the binding of CD36 to the epitope structure of oxLDL. Moreover, the binding of baicalein to CD36 enhanced the cholesterol efflux via the CD36-Src-JNK-ABCA1 signalling pathway. Meanwhile, Src and JNK inhibitors reversed the baicalein-induced reduction in cholesterol accumulation. In conclusion, these findings suggested that baicalein as a food supplement could inhibit macrophage foam cell formation and play an anti-atherosclerosis effect.